Implementasi Penggunaan Media Kartu Muatan dalam Meningkatkan Hasil Belajar Matematika Bilangan Bulat di Kelas V MI Salafiyah Syafi’iyah - Firdausi, Durratul; Rosa Linda Yonita; Abdul Wafi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted based on the low mathematical learning outcomes of fifth-grade students at MI Salafiyah Syafi'iyah School regarding integers. Students struggled to understand the concepts of positive and negative numbers, as well as integer addition and subtraction, due to the abstract nature of the subject and the use of traditional teaching methods. This study aims to determine the learning outcomes before and after using the content card media to improve the mathematics learning outcomes of integer material. The research uses the Kemmis and Mc Taggart model Class Action Research (PTK) approach which is carried out in two cycles. The research subjects amounted to 30 students in class V of MI Salafiyah Syafi'iyah. The data collection technique is carried out through learning outcome tests. The results of the study showed an increase in student learning outcomes in each cycle. In the pre-section, classical learning completeness only reached 27% with an average score of 58.4. After the application of the charge card media in cycle I, classical completeness increased to 76% with an average value of 75.2. In cycle II, classical completeness reached 100% with an average score of 91.4. The results of the study showed that the use of positive and negative charge card media could improve the learning outcomes of mathematics integer material in grade V students of MI Salafiyah Syafi'iyah.